2005
DOI: 10.21273/jashs.130.5.722
|View full text |Cite
|
Sign up to set email alerts
|

Simple Sequence Repeat (SSR) Markers for Genetic Mapping of Raspberry and Blackberry

Abstract: Interest in molecular markers and genetic maps is growing among researchers developing new cultivars of Rubus L. (raspberry and blackberry). Several traits of interest fail to express in seedlings or reliably in some environments and are candidates for marker-assisted selection. A growing number of simple sequence repeat (SSR) molecular markers derived from Rubus and Fragaria L. (strawberry) are available for use with Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 43 publications
1
26
0
Order By: Relevance
“…It is probable that parasitoids will operate more effectively within the confines of such tunnels, having smaller areas to search for aphid prey and reduced ability to disperse from the tunnel. Second, the development of molecular and genetic tools, including amplified fragment length polymorphism molecular markers and simple sequence repeat microsatellite markers, has recently led to much better understanding of resistance mechanisms in Rubus (Graham et al , 2002; Graham et al , 2004; Stafne et al , 2005; Sargent et al , 2007) and may lead to more durable resistance against A. idaei . If the problem of fruit contamination with aphid mummies can be overcome, these twin approaches of bottom‐up (host plant resistance) and top‐down control (biocontrol agents) might therefore lead to more effective and sustainable control of A. idaei in the future.…”
Section: Discussionmentioning
confidence: 99%
“…It is probable that parasitoids will operate more effectively within the confines of such tunnels, having smaller areas to search for aphid prey and reduced ability to disperse from the tunnel. Second, the development of molecular and genetic tools, including amplified fragment length polymorphism molecular markers and simple sequence repeat microsatellite markers, has recently led to much better understanding of resistance mechanisms in Rubus (Graham et al , 2002; Graham et al , 2004; Stafne et al , 2005; Sargent et al , 2007) and may lead to more durable resistance against A. idaei . If the problem of fruit contamination with aphid mummies can be overcome, these twin approaches of bottom‐up (host plant resistance) and top‐down control (biocontrol agents) might therefore lead to more effective and sustainable control of A. idaei in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The transferability of F. × ananassa loci to Rubus species was moderate: 46.7% in Nordic species, 40% in red raspberry and hybrids, and 33.3% in black raspberry and blackberry (33.3%). Other authors [20,62] reported even a lower transferability from F. × ananassa to diploid red and black raspberries (Idaeobatus subgenus, 8-23%) than to tetraploid blackberry (Rubus subgenus, 26-36%). Only two of the 15 strawberry markers were polymorphic in raspberries (FaFS01 and FaCH01) and five markers if all Rubus species were taken into account.…”
Section: Choice Of Cultivars and Transferability Of Ssr Markersmentioning
confidence: 91%
“…AFLPs [14] have become a useful tool for generating maps of large numbers of dominant markers without prior knowledge of DNA sequence [15], although their subsequent application as markers for selection of useful traits is limited to the breeding lines in which they were generated, unless they are first converted to SCARs [16]. Owing to their codominant nature and ease of transferability between germplasm, microsatellite markers (simple sequence repeats; SSRs), have found utility for a variety of purposes including the development of transferable, saturated linkage maps in many rosaceous genera [17-19], and SSRs have recently been developed for Rubus [20-22]. …”
Section: Introductionmentioning
confidence: 99%